EXPLORING THE APPLICATION OF THE ESSENTIAL ELEMENTS OF DANCECREATIVITY IN DANCE EDUCATION - Ya-Fen, Chen (E-Journal VFU, 2024)
he purpose of this research is to try to implement the concept ofchoreography in the dance curriculum, which uses the introduction and guidance of the basicelements of choreography and adds the concepts of trajectory, level and relationship to inspirestudents to think about choreography, which can be integrated into the dance curriculum as a217stimulus for thinking about choreography
Keywords: Curriculum; Dance education; Dance creativity